Differences in radionuclide and heavy metal concentrations found in the kidneys of barren-ground caribou from the western Northwest Territories 1994/95 to 2000/01 - Larter, Nicholas C.; Nagy, John A.; Elkin, Brett T.; Macdonald, Colin R. (Rangifer, 2010)
Aluminum, nickel, cadmium, mercury, and lead concentrations were measured in the kidney tissue of known aged barren-ground caribou wintering in the western Northwest Territories harvested during winter 1994/1995 and during winters 2000/2001 and 2001/2002. 40K, 137Cs, and 210Pb concentrations were measured in the kidney tissue of known aged barren-ground caribou during winter 2000/2001 and compared to concentrations in winter 1993/1994 reported in Macdonald et al. (1996). Renal concentrations of aluminum were higher (P<0.001)in winter 2000/2001 than winter 1994/1995. Contrastingly renal concentrations of mercury were lower (P<0.001) in winter 2000/2001 than 1994/1995. 137Cs (P<0.02), 40K (P=0.01), 210Pb (P<0.01) had lower renal concentrations in winter 2000/2001 than 1993/1994. Renal concentrations of cadmium (P<0.001) and 137Cs (P<0.04) had a positive relationship with caribou age. We also document renal concentrations of arsenic, copper, selenium, zinc, 232Th, 226Ra, and 235U in the kidneys of caribou harvested in winters 2000/2001 and 2001/2002. Renal zinc concentrations were positively correlated with the age of caribou.